Recent Developments in Rare-Earths Doped Nano-Engineered Glass Based Optical Fibers for High Power Fiber Lasers. Issue 4 (1st October 2016) - Paul, Mukul C.; Bysakh, S.; Das, Shyamal; Dhar, Anirban; Pal, M.; Bhadra, S. K.; Sahu, J. K.; Kir'yanov, A. V.; d'Acapito, F.
ABSTRACT: Recent advances of development of rare-earth (RE) doped optical fibers have become increasingly important due to their applications in various optoelectronic devices such as high power optical fiber amplifiers, fiber lasers, etc. We present a review of recent progress on development of RE-doped glass host based optical fiber materials with special emphasis on large mode area fibers for efficient laser and amplifier. The challenging task is to manage high power inside the active core otherwise output power instability would affect the beam quality. Best solution is to use suitable dopants in addition to active elements during the process of fabrication. Modified chemical vapour deposition (MCVD) process combined with solution doping technique is deployed to develop RE-doped nano-engineered glass based optical fibers through suitable thermal annealing of optical preforms. The developed doped fibers are characterized by DTA, TEM, XRD, XAS, EPMA and EXAFS to assess the structural parameters. This new class of optical fiber materials will open up new possibilities for extended functionality and greater optoelectronic integration. GRAPHICAL ABSTRACT: